PSAK 409 Implementation in ZIS Management: Evidence from LAZISNU and BAZNAS in Metro City Through the Lens of Shariah Enterprise Theory - Rani Asupa; Anggoro Sugeng; Thoyibatun Nisa; Witantri Dwi Swandini; Dewi Mustika (Nuban Jagadhita Centre, 2026)
Purpose: This study aims to analyze the implementation of PSAK 409 at BAZNAS and LAZISNU in Metro City. In this study, PSAK 409 serves as the technical accounting framework, while SET functions as the philosophical foundation that instills a spirit of accountability within the Islamic financial reporting cycle, to identify two typologies of adaptation patterns when compared with the standards and theories of SET. Methodology: The research method employed was a descriptive qualitative approach using a collective study design conducted at BAZNAS and LAZISNU in Metro City. Data analysis was performed using the Miles and Huberman model, which includes the stages of data reduction, narrative data presentation, and drawing conclusions. Findings: The results show that the implementation of PSAK 409 at both institutions exhibits adaptation typologies that are contrasting yet complementary. BAZNAS represents a formal adaptation typology based on compliance with a centralized digital system (SIMBA), but faces challenges regarding the accessibility of public information. Conversely, LAZISNU represents a cultural adaptation typology based on social capital. However, it has not yet technically implemented the standard instruments of PSAK 409 and relies on manual record-keeping. From a SET perspective, the technical weaknesses in LAZISNU’s asset record-keeping reduce the completeness of vertical accountability, while BAZNAS is constrained by the lack of accessibility to financial reports, which undermines the fulfillment of the public’s right to transparency in the dimension of horizontal accountability.